Ceramic coating for gravure etching pot and coating method thereof
By using ceramic coatings made of nanosilica sol, inorganic pigment, modified silica filler and hollow glass microbeads on the etching pot, poor wear resistance and PFAS usage restrictions are solved. The problem of this has achieved high hardness, wear resistance and environmentally friendly coating effects.
Patent Information
- Application Number
- CN202510034857.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The polytetrafluoroethylene non-stick coatings used in existing etching pots have poor wear resistance. At the same time, due to the PFAS content, they are restricted by European and American countries, and alternatives need to be found.
A ceramic coating consisting of a primer and a topcoat consisting of nanosilica sol, inorganic pigment, modified silica filler and hollow glass microbeads. The topcoat contains nanosilica sol and hollow glass microbeads. Beads form high hardness, wear-resistant coatings through spraying, polishing and grinding processes.
It achieves high hardness and wear resistance of ceramic coatings, extends the service life of the etching pot, and avoids the use of PFAS, which meets environmental protection requirements.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic coatings and relates to a ceramic coating for a gravure etching pot and a coating method thereof. Background Art
[0002] The main components of ceramic coatings are similar to those of ceramic glazes, mostly inorganic-organic composite coatings composed of metal oxides, non-metal oxides and a small amount of polyalkoxyorganosilane. The coating is a two-component package, which is mixed, cured, sprayed and baked at high temperature before use to form a high-hardness enamel-like coating. The physical and chemical properties and appearance of the material are similar to those of ceramics, so it is called "ceramic coatings."
[0003] Ceramic coatings have excellent performance characteristics and energy-saving and environmental protection advantages. With the continuous improvement and development of its technology and products, its application areas are not only limited to kitchen utensils such as non-stick pans, rice cookers, baking trays, heaters, small household appliances, electric irons, and automobile wheels, but are also developing into architectural decoration curtain walls, fireproof material panels, subway high-speed rail coatings, tunnel coatings, bridge coatings, medical environment coatings, metallurgical water conservancy and electric power engineering, marine engineering, ship engineering and other architectural decoration and industrial protective materials.
[0004] Etched pot is a new type of pot. The inner surface of the stainless steel pot is made into a honeycomb mesh texture by etching, which alleviates the poor wear resistance of polytetrafluoroethylene non-stick coating. Conventional etched pots are coated with polytetrafluoroethylene non-stick coating, and polytetrafluoroethylene belongs to PFAS. At present, European and American countries are actively legislating to prohibit or restrict the use of materials and products containing PFAS. Ceramic non-stick coating is the best alternative to polytetrafluoroethylene non-stick coating. Summary of the invention
[0005] The object of the present invention is to provide a ceramic coating for a gravure etching pot and a coating method thereof, which has the characteristics of wear resistance and stain resistance.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A ceramic coating for a gravure etching pot, comprising a primer and a topcoat, The formula of the primer is as follows: by mass percentage, 20-30% of nano-silica sol, 5-15% of inorganic pigment, 5-10% of modified silica filler, 5-10% of hollow glass microspheres, 30-40% of methyldimethoxysilane, 5-10% of methyltrimethoxysilane, 1-5% of formic acid, and 5-10% of deionized water; The preparation method of the modified silica filler is as follows: silica and silicon carbide are mixed in a mass ratio of 4:1, ground in a ball mill at a speed of 400r / min for 2h to obtain a mixture with a particle size of 200 mesh, ethylene glycol and glycerol are mixed in a volume ratio of 1:1 to obtain a mixed solution, the mixture is immersed in the mixed solution to obtain a solid-liquid mixture with a mass fraction of 30%, after ultrasonication for 2h, filtered, the solid is collected, washed with deionized water, and dried at 70°C for 12h, and the dried solid is dispersed again in a sodium silicate solution with a mass fraction of 30%, the mass ratio of the solid to sodium silicate is 1:1, after ultrasonication for 1h, filtered, and dried at 60°C for 24h to obtain the modified silica filler; The formula of the topcoat is as follows: by mass percentage, 20-30% nano-silica sol, 5-10% hollow glass microspheres, 30-40% methyldimethoxysilane, 5-10% methyltrimethoxysilane, 1-5% formic acid, 1-5% polydimethylsiloxane, and 10-20% deionized water.
[0007] Furthermore, the particle size of the hollow glass microbeads in the primer and topcoat is ≤10 μm.
[0008] Further, the preparation method of the primer is as follows: S1.1: Grind the inorganic pigment and modified silica filler in a ball mill at a ratio of 400 r / min at 20-25°C for 1-2 h to obtain a mixed powder; S1.2: Disperse the mixed powder and hollow glass microspheres in nano-silica sol, perform ultrasonic treatment for 2-3 hours, and obtain primer component A after dispersion; S1.3: Formic acid and deionized water are mixed in proportion to obtain a primer C component, methyldimethoxysilane, methyltrimethoxysilane and polydimethylsiloxane are mixed in proportion, and the mixture is put into a mixer and stirred at a speed of 200 r / min for 20 min to obtain a primer B component; S1.4: Add primer C component to primer B component to obtain primer B+C component, stir primer A component at a speed of 120-140 r / min, add primer B+C component after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the primer.
[0009] Further, the preparation method of the topcoat is as follows: S2.1: Disperse hollow glass microspheres in nano-silica sol in proportion at 20-25°C, perform ultrasonic treatment for 2-3 hours, and obtain topcoat component A after dispersion; S2.2: put methyldimethoxysilane, methyltrimethoxysilane, formic acid, polydimethylsiloxane and deionized water into a mixer in proportion and stir at a speed of 200 r / min for 10 to 20 min to obtain topcoat component B; S2.3: The topcoat component A is stirred at a speed of 120-140 r / min, and after stirring for 0.5 h, the topcoat component B is added and continued to be stirred at a speed of 120 r / min for 5 h. The stirred mixture is filtered using a filter cloth with a mesh size of 300 or more to obtain the topcoat.
[0010] A method for coating a ceramic coating for a gravure etching pot, wherein the ceramic coating coating method is as follows: S3.1: First spray the primer on the surface of the gravure etched pot, the spraying parameters are spraying distance 60mm, spraying rate 80 mm / s; S3.2: Spray the topcoat directly after spraying the primer. The spraying parameters are spraying distance 40 mm, spraying rate 60 mm / s, standing for 5 hours after spraying, and drying at 80℃ for 5 minutes; S3.3: After the topcoat is dried, the surface of the gravure etched pot is polished and ground. First, a grinding head composed of 500 mesh elastic modules is used for grinding for 20 seconds, and then a grinding head composed of 2000 mesh elastic modules is used for grinding for 10 to 30 seconds. After grinding, baking and curing treatment is performed again to complete the coating operation.
[0011] Furthermore, the thickness of the primer sprayed in S3.1 is 20-30 μm.
[0012] Furthermore, the thickness of the topcoat sprayed in S3.2 is 8-12 μm.
[0013] Furthermore, the pressure applied by the grinding head of the hard grinding block for polishing in S3.3 to the surface of the tile is 1.5 MPa, and the pressure applied by the grinding head composed of the elastic module to the surface of the tile is 0.3~0.5 MPa.
[0014] Furthermore, the parameters for the baking and curing in S3.3 are first baking at 100° C. for 7 minutes in the low temperature section and then baking at 300° C. for 15 minutes.
[0015] The ceramic coating of the invention comprises a primer and a topcoat. In the primer, nano silica sol, inorganic pigment and modified silica filler together form a solid primer layer, which enhances the adhesion between the coating and the substrate and improves the wear resistance of the coating. Methyldimethoxysilane and methyltrimethoxysilane are stable at high temperatures and help to improve the overall temperature resistance of the coating. The addition of hollow glass microspheres can adjust the density and hardness of the coating and help to improve the thermal insulation performance of the coating. By adjusting the content of formic acid and deionized water, the viscosity of the coating can be optimized, making it easier to construct and apply.
[0016] The nano silica sol in the primer of the present invention serves as a film-forming substance, provides the main structure of the coating, and can enhance the hardness and wear resistance of the coating; the inorganic pigment gives the coating color and has certain hiding power and durability; the hollow glass microspheres can adjust the coating performance, such as density, hardness and heat insulation, and can help reduce the shrinkage of the coating, reduce the density and wear resistance of the coating, make the coating easier to pulverize during polishing and grinding, and form a more neat cutting edge; methyldimethoxysilane and methyltrimethoxysilane serve as cross-linking agents, and react with the nano silica sol under acidic conditions to form a linear molecular structure, reduce the network cross-linking structure, improve the flexibility of the coating, reduce the hardness and brittleness, and effectively avoid cracking and porcelain explosion during polishing and grinding; formic acid serves as a catalyst to promote the hydrolysis and polycondensation reaction of silane and adjust the pH value of the coating.
[0017] In order to better increase the solid content of the coating, improve the density and weather resistance of the coating, the present invention further modifies the silica filler, and the hydroxyl groups (-OH) in the ethylene glycol and glycerol molecules can hydrogen bond with the hydroxyl groups on the surface of the silica, thereby forming an organic coating layer on the surface of the silica particles. This coating layer can change the surface polarity, hydrophilicity and surface energy of the silica particles, and improve its compatibility with the polymer matrix; the addition of sodium silicate solution can further form a chemically bonded silane layer on the surface of the silica filler, and this silane layer can react with functional groups such as hydroxyl groups on the surface of the substrate, thereby forming a stronger binding force.
[0018] The present invention uses ethylene glycol and glycerol in a mixed manner during the modification process. Both ethylene glycol and glycerol are common organic solvents, each of which has certain polarity and functional groups and can interact with the surface of silicon dioxide. The mixed use of the two can combine the advantages of the two and achieve a better modification effect. Compared with the use of ethylene glycol or glycerol alone, the mixed ethylene glycol and glycerol molecules can be more evenly covered on the surface of silicon dioxide to form a denser coating layer, thereby improving the dispersibility and stability of silicon dioxide; ethylene glycol and glycerol have a synergistic effect during the modification process, and they can act together on the surface of silicon dioxide, and through physical adsorption and chemical bonding, the subsequent modifier is more firmly combined on the surface of silicon dioxide. This synergistic effect helps to enhance the performance of the modified silicon dioxide filler, such as improving its dispersibility and compatibility in the polymer matrix.
[0019] The surface properties of the modified silica filler are improved, and its compatibility with other components in the coating is enhanced, thereby improving its dispersibility in the primer, which helps to avoid filler agglomeration in the coating and ensure the uniformity and stability of the coating; the active groups on the surface of the modified silica filler can form chemical bonds with the surface of the substrate, thereby enhancing the adhesion between the primer and the substrate. This helps prevent the coating from peeling and cracking and prolongs the service life of the coating; in addition, the modified silica filler can form a dense protective film that effectively prevents corrosive media such as oxygen, water, oil, steam, and organic matter from penetrating into the substrate, thereby enhancing the corrosion resistance of the coating.
[0020] The addition of polydimethylsiloxane in the topcoat significantly improves the non-stickiness of the coating, making the surface smoother and easier to clean; the combination of nano-silica sol, methyldimethoxysilane and methyltrimethoxysilane ensures the stability of the coating under high temperature and friction conditions.
[0021] In the coating process of the present invention, by setting a specific spraying distance and spraying rate, the uniform distribution of the coating can be ensured, the problem of uneven thickness can be avoided, and the overall quality of the coating can be improved; each layer of coating is subjected to a static and drying treatment after spraying, which is conducive to the full volatilization of the solvent in the coating and the initial solidification of the coating, and the bonding force between the coating and the substrate is enhanced; the polishing and grinding steps use elastic modules with different mesh sizes, first coarse and then fine, and gradually improve the surface finish. This not only helps to improve the appearance texture of the coating, but also further improves the anti-sticking performance and wear resistance of the coating.
[0022] Beneficial effects of the present invention: In the preparation of the primer of the present invention, under acidic conditions, methyldimethoxysilane and methyltrimethoxysilane will undergo a hydrolysis reaction to generate silanol groups. These silanol groups then undergo a polycondensation reaction with the hydroxyl groups on the surface of the nano-silica sol to form Si-O-Si bonds and linear molecular structures, reduce the network cross-linking structure, improve the flexibility of the coating, reduce the hardness and brittleness, and effectively avoid cracking and porcelain explosion during polishing. In this process, the nano-silica sol, inorganic pigments and modified silica fillers serve as the skeleton of the coating, and silane serves as a cross-linking agent to connect these skeletons together. The addition of hollow glass microspheres can fine-tune the performance of the primer coating through its special structure; The ceramic coating has high hardness and can effectively resist wear and tear, thus extending the service life of the cookware. After polishing and grinding, the coating surface is highly smooth, not easy to adhere to food, and easy to clean. The ceramic coating can maintain its performance stability in a high temperature environment and is not easy to fall off or deteriorate. The surface of the coating after polishing and grinding is as smooth as a mirror and has a good visual effect. DETAILED DESCRIPTION
[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0024] Primer ratio 1: nano silica sol 25%, inorganic pigment 10%, modified silica filler 10%, hollow glass microspheres 10%, methyl dimethoxy silane 30%, methyl trimethoxy silane 5%, formic acid 5%, deionized water 5%; Primer ratio 2: nano silica sol 20%, inorganic pigment 5%, modified silica filler 5%, hollow glass microspheres 5%, methyl dimethoxy silane 40%, methyl trimethoxy silane 10%, formic acid 5%, deionized water 10%; Primer ratio 3: nano silica sol 30%, inorganic pigment 15%, modified silica filler 5%, hollow glass microspheres 5%, methyl dimethoxy silane 30%, methyl trimethoxy silane 5%, formic acid 1%, deionized water 9%; Topcoat ratio 1: 25% nano silica sol, 10% hollow glass microspheres, 40% methyl dimethoxy silane, 5% methyl trimethoxy silane, 5% formic acid, 5% polydimethylsiloxane, 10% deionized water; Topcoat ratio 2: nano silica sol 20%, hollow glass microspheres 10%, methyl dimethoxy silane 40%, methyl trimethoxy silane 8%, formic acid 1%, polydimethylsiloxane 1%, deionized water 20%; Topcoat ratio 3: 30% nano silica sol, 5% hollow glass microspheres, 30% methyl dimethoxy silane, 10% methyl trimethoxy silane, 5% formic acid, 5% polydimethylsiloxane, 15% deionized water; Among them, the preparation method of the modified silica filler is as follows: silica and silicon carbide are mixed in a mass ratio of 4:1, ground in a ball mill at a speed of 400r / min for 2h to obtain a mixture with a particle size of 200 mesh, ethylene glycol and glycerol are mixed in a volume ratio of 1:1 to obtain a mixed solution, and the mixture is immersed in the mixed solution to obtain a solid-liquid mixture with a mass fraction of 30%, and after ultrasonication for 2h, filtered, the solid is collected, washed with deionized water, and dried at 70°C for 12h, and the dried solid is dispersed again in a sodium silicate solution with a mass fraction of 30%, and the mass ratio of the solid to sodium silicate is 1:1. After ultrasonication for 1h, filtered, and dried at 60°C for 24h to obtain the modified silica filler.
[0025] Example 1 The preparation method of the primer is as follows: S1.1: grind the inorganic pigment and modified silica filler in a ball mill at a ratio of 1 to the primer at 25°C, with the speed of the ball mill being 400 r / min and the grinding time being 2 h to obtain a mixed powder; S1.2: Disperse the mixed powder and hollow glass microspheres in nano-silica sol, perform ultrasonic treatment for 2-3 hours, and obtain primer component A after dispersion; S1.3: Mix formic acid and deionized water according to the primer ratio 1 to obtain a primer C component, mix methyldimethoxysilane, methyltrimethoxysilane and polydimethylsiloxane according to the ratio, put them into a stirrer and stir them at a speed of 200 r / min for 20 minutes to obtain a primer B component; S1.4: Add primer C component to primer B component to obtain primer B+C component, stir primer A component at a speed of 120-140 r / min, add primer B+C component after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the primer.
[0026] The preparation method of the topcoat is as follows: S2.1: Disperse hollow glass microspheres in nano-silica sol at a topcoat ratio of 1 at 25°C, perform ultrasonic treatment for 2-3 hours, and obtain topcoat component A after dispersion; S2.2: according to the topcoat ratio 1, methyldimethoxysilane, methyltrimethoxysilane, formic acid, polydimethylsiloxane and deionized water are placed in a mixer and stirred at a speed of 200 r / min for 10 min to obtain topcoat component B; S2.3: The topcoat component A is stirred at a speed of 130 r / min, and after stirring for 0.5 h, the topcoat component B is added and continued to be stirred at a speed of 120 r / min for 5 h. The stirred mixture is filtered using a filter cloth with a mesh size of 300 or more to obtain the topcoat.
[0027] The ceramic coating coating method is as follows: S3.1: First spray the primer on the surface of the gravure etched pot, the spraying parameters are spraying distance 60mm, spraying rate 80 mm / s, and the thickness of the primer spray is 25μm; S3.2: After spraying the primer, directly spray the topcoat. The spraying parameters are spraying distance 40mm, spraying rate 60 mm / s, standing for 5h after spraying, drying at 80℃ for 5min, and the thickness of the topcoat spray is 10μm. S3.3: After the topcoat has dried, the surface of the gravure etched pot is polished and ground. First, a grinding head composed of 500 mesh elastic modules is used for grinding for 20 seconds. The pressure applied by the grinding head of the hard grinding block to the tile surface is 1.5 MPa. Then, a grinding head composed of 2000 mesh elastic modules is used for grinding for 20 seconds. The pressure applied by the grinding head composed of the elastic modules to the tile surface is 0.4 MPa. After grinding, baking and curing treatment is performed again. The baking and curing parameters are first baking at 100°C for 7 minutes in the low temperature section, and then baking at 300°C for 15 minutes to complete the coating operation.
[0028] Example 2 The preparation method of the primer is as follows: S1.1: grind the inorganic pigment and modified silica filler in a ball mill at a primer ratio of 2 at 20°C, with the ball mill speed at 400 r / min and the grinding time at 1 h to obtain a mixed powder; S1.2: Disperse the mixed powder and hollow glass microspheres in nano-silica sol, perform ultrasonic treatment for 2 h, and obtain primer component A after dispersion; S1.3: Mix formic acid and deionized water according to the primer ratio 2 to obtain a primer C component, mix methyldimethoxysilane, methyltrimethoxysilane and polydimethylsiloxane according to the ratio, put them into a stirrer and stir them at a speed of 200 r / min for 20 minutes to obtain a primer B component; S1.4: Add primer C component to primer B component to obtain primer B+C component, stir primer A component at a speed of 120-140 r / min, add primer B+C component after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the primer.
[0029] The preparation method of the topcoat is as follows: S2.1: Disperse hollow glass microspheres in nano-silica sol at a topcoat ratio of 2 at 20°C, perform ultrasonic treatment for 2 hours, and obtain topcoat component A after dispersion; S2.2: according to the topcoat ratio 2, methyldimethoxysilane, methyltrimethoxysilane, formic acid, polydimethylsiloxane and deionized water are placed in a mixer and stirred at a speed of 200 r / min for 20 min to obtain a topcoat component B; S2.3: The topcoat component A is stirred at a speed of 120 r / min, and after stirring for 0.5 h, the topcoat component B is added and continued to be stirred at a speed of 120 r / min for 5 h. The stirred mixture is filtered using a filter cloth with a mesh size of 300 or more to obtain the topcoat.
[0030] The ceramic coating coating method is as follows: S3.1: First spray the primer on the surface of the gravure etched pot, the spraying parameters are spraying distance 60mm, spraying rate 80 mm / s, and the thickness of the primer spray is 20μm; S3.2: Spray the topcoat directly after spraying the primer. The spraying parameters are spraying distance 40 mm, spraying rate 60 mm / s, standing for 5 hours after spraying, drying at 80℃ for 5 minutes, and the thickness of the topcoat spray is 8μm; S3.3: After the topcoat is dried, the surface of the gravure etched pot is polished and ground. First, a grinding head composed of 500 mesh elastic modules is used for grinding for 20 seconds. The pressure applied by the grinding head of the hard grinding block to the tile surface is 1.5 MPa. Then, a grinding head composed of 2000 mesh elastic modules is used for grinding for 10 seconds. The pressure applied by the grinding head composed of the elastic modules to the tile surface is 0.3 MPa. After grinding, baking and curing treatment is performed again. The baking and curing parameters are first baking at 100°C for 7 minutes in the low temperature section, and then baking at 300°C for 15 minutes to complete the coating operation.
[0031] Example 3 The preparation method of the primer is as follows: S1.1: grind the inorganic pigment and modified silica filler in a ball mill at a primer ratio of 3 at 25°C, with a ball mill speed of 400 r / min and a grinding time of 1 h to obtain a mixed powder; S1.2: Disperse the mixed powder and hollow glass microspheres in nano-silica sol, perform ultrasonic treatment for 2-3 hours, and obtain primer component A after dispersion; S1.3: Mix formic acid and deionized water according to the primer ratio 3 to obtain a primer C component, mix methyldimethoxysilane, methyltrimethoxysilane and polydimethylsiloxane according to the ratio, put them into a stirrer and stir them at a speed of 200 r / min for 20 minutes to obtain a primer B component; S1.4: Add primer C component to primer B component to obtain primer B+C component, stir primer A component at a speed of 120-140 r / min, add primer B+C component after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the primer.
[0032] The preparation method of the topcoat is as follows: S2.1: Disperse hollow glass microspheres in nano-silica sol at a topcoat ratio of 3 at 25°C, perform ultrasonic treatment for 3 hours, and obtain topcoat component A after dispersion; S2.2: according to the topcoat ratio of 3, methyldimethoxysilane, methyltrimethoxysilane, formic acid, polydimethylsiloxane and deionized water are placed in a mixer and stirred at a speed of 200 r / min for 10 min to obtain a topcoat component B; S2.3: The topcoat component A is stirred at a speed of 140 r / min, and after stirring for 0.5 h, the topcoat component B is added and continued to be stirred at a speed of 120 r / min for 5 h. The stirred mixture is filtered using a filter cloth with a mesh size of 300 or more to obtain the topcoat.
[0033] The ceramic coating coating method is as follows: S3.1: First spray the primer on the surface of the gravure etching pot, the spraying parameters are spraying distance 60mm, spraying rate 80 mm / s, and the thickness of the primer spray is 30μm; S3.2: Spray the topcoat directly after spraying the primer. The spraying parameters are spraying distance 40 mm, spraying rate 60 mm / s, standing for 5 hours after spraying, drying at 80℃ for 5 minutes, and the thickness of the topcoat spray is 12μm; S3.3: After the topcoat is dried, the surface of the gravure etched pot is polished and ground. First, a grinding head composed of 500 mesh elastic modules is used for grinding for 20 seconds. The pressure applied by the grinding head of the hard grinding block to the tile surface is 1.5 MPa. Then, a grinding head composed of 2000 mesh elastic modules is used for grinding for 30 seconds. The pressure applied by the grinding head composed of the elastic modules to the tile surface is 0.5 MPa. After grinding, baking and curing treatment is performed again. The baking and curing parameters are first baking at 100°C for 7 minutes in the low temperature section, and then baking at 300°C for 15 minutes to complete the coating operation.
[0034] Comparative Example 1 In this comparative example, the silica filler in the primer is not modified, and the remaining steps are consistent with those in Example 1.
[0035] Comparative Example 2 In this comparative example, no mixture of ethylene glycol and glycerol was used in the silicon dioxide modification process, only ethylene glycol was used, and the remaining steps were consistent with those of Example 1.
[0036] Comparative Example 3 In this comparative example, no mixture of ethylene glycol and glycerol was used in the silicon dioxide modification process, only glycerol was used, and the remaining steps were consistent with Example 1.
[0037] Comparative Example 4 In this comparative example, sodium silicate modification is not used in the silicon dioxide modification process, and the remaining steps are consistent with Example 1.
[0038] Comparative Example 5 In this comparative example, the surface of the gravure etching pot after drying is not polished or ground, and the remaining steps are consistent with those in Example 1.
[0039] Comparative Example 6 In this comparative example, the surface of the gravure etching pot after grinding is not subjected to baking and curing treatment, and the remaining steps are consistent with those in Example 1.
[0040]
[0041]
[0042] The experimental results show that modifying the silica filler in the primer can effectively improve the wear resistance, acid and alkali resistance and hot and cold shock resistance of the coating; polishing and grinding and baking and curing the surface of the gravure etched pot can effectively improve the wear resistance and stain resistance of the ceramic coating.
[0043] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A ceramic coating for gravure etching pots, characterized in that: The ceramic coating comprises a primer and a topcoat. The formula of the primer is as follows: by mass percentage, 20-30% of nano-silica sol, 5-15% of inorganic pigment, 5-10% of modified silica filler, 5-10% of hollow glass microspheres, 30-40% of methyldimethoxysilane, 5-10% of methyltrimethoxysilane, 1-5% of formic acid, and 5-10% of deionized water; The preparation method of the modified silica filler is as follows: silica and silicon carbide are mixed in a mass ratio of 4:1, ground in a ball mill at a speed of 400r / min for 2h to obtain a mixture with a particle size of 200 mesh, ethylene glycol and glycerol are mixed in a volume ratio of 1:1 to obtain a mixed solution, the mixture is immersed in the mixed solution to obtain a solid-liquid mixture with a mass fraction of 30%, after ultrasonication for 2h, filtered, the solid is collected, washed with deionized water, and dried at 70°C for 12h, and the dried solid is dispersed again in a sodium silicate solution with a mass fraction of 30%, the mass ratio of the solid to sodium silicate is 1:1, after ultrasonication for 1h, filtered, and dried at 60°C for 24h to obtain the modified silica filler; The formula of the topcoat is as follows: by mass percentage, 20-30% nano-silica sol, 5-10% hollow glass microspheres, 30-40% methyldimethoxysilane, 5-10% methyltrimethoxysilane, 1-5% formic acid, 1-5% polydimethylsiloxane, and 10-20% deionized water.
2. A ceramic coating for gravure etching pots according to claim 1, characterized in that: The particle size of the hollow glass microbeads in the primer and topcoat is ≤10 μm.
3. A ceramic coating for gravure etching pots according to claim 1, characterized in that: The preparation method of the primer is as follows: S1.1: Grind the inorganic pigment and modified silica filler in a ball mill at a ratio of 400 r / min at 20-25°C for 1-2 h to obtain a mixed powder; S1.2: Disperse the mixed powder and hollow glass microspheres in nano-silica sol, perform ultrasonic treatment for 2-3 hours, and obtain primer component A after dispersion; S1.3: Formic acid and deionized water are mixed in proportion to obtain a primer C component, methyldimethoxysilane, methyltrimethoxysilane and polydimethylsiloxane are mixed in proportion, and the mixture is put into a mixer and stirred at a speed of 200 r / min for 20 min to obtain a primer B component; S1.4: Add primer C component to primer B component to obtain primer B+C component, stir primer A component at a speed of 120-140 r / min, add primer B+C component after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the primer.
4. The ceramic coating for gravure etching pot according to claim 1, characterized in that: The preparation method of the topcoat is as follows: S2.1: Disperse hollow glass microspheres in nano-silica sol in proportion at 20-25°C, perform ultrasonic treatment for 2-3 hours, and obtain topcoat component A after dispersion; S2.2: put methyldimethoxysilane, methyltrimethoxysilane, formic acid, polydimethylsiloxane and deionized water into a mixer in proportion and stir at a speed of 200 r / min for 10 to 20 min to obtain topcoat component B; S2.3: The topcoat component A is stirred at a speed of 120-140 r / min, and after stirring for 0.5 h, the topcoat component B is added and continued to be stirred at a speed of 120 r / min for 5 h. The stirred mixture is filtered using a filter cloth with a mesh size of 300 or more to obtain the topcoat.
5. A coating method for a ceramic coating for a gravure etched pot, based on the ceramic coating for a gravure etched pot according to any one of claims 1 to 4, characterized in that: The ceramic coating coating method is as follows: S3.1: First spray the primer on the surface of the gravure etched pot, the spraying parameters are spraying distance 60mm, spraying rate 80 mm / s; S3.2: Spray the topcoat directly after spraying the primer. The spraying parameters are spraying distance 40 mm, spraying rate 60 mm / s, standing for 5 hours after spraying, and drying at 80℃ for 5 minutes; S3.3: After the topcoat is dried, the surface of the gravure etched pot is polished and ground. First, a grinding head composed of 500 mesh elastic modules is used for grinding for 20 seconds, and then a grinding head composed of 2000 mesh elastic modules is used for grinding for 10 to 30 seconds. After grinding, baking and curing treatment is performed again to complete the coating operation.
6. A method for coating a ceramic coating for a gravure etching pot according to claim 5, characterized in that: The thickness of the primer sprayed in S3.1 is 20-30 μm.
7. The method for coating a ceramic coating for a gravure etching pot according to claim 5, characterized in that: The thickness of the topcoat sprayed in S3.2 is 8-12 μm.
8. The method for coating a ceramic coating for a gravure etching pot according to claim 5, characterized in that: The pressure applied by the grinding head of the polishing hard grinding block in S3.3 to the surface of the tile is 1.5 MPa.
9. The method for coating a ceramic coating for a gravure etching pot according to claim 5, characterized in that: The pressure applied by the grinding head composed of the polishing elastic module in S3.3 to the surface of the tile is 0.3~0.5MPa.
10. The method for coating a ceramic coating for a gravure etching pot according to claim 5, characterized in that: The parameters for the baking and curing in S3.3 are first baking at 100° C. for 7 minutes at a low temperature, and then baking at 300° C. for 15 minutes.
Citation Information
Patent Citations
High-adhesion impact-resistant ceramic coating and preparation method and application thereof
CN113292916A
Matt ceramic coating and preparation method thereof
CN117866464A
Cited By
A high-strength and high-toughness ceramic coating and its use method
CN119752323A
High-performance ceramic coating as well as preparation method and spraying method thereof
CN120383877A
Sand-blasting-free ceramic coating as well as preparation method and spraying method thereof
CN120484684A